PENGARUH WORKING CAPITAL TURNOVER, INVENTORY TURNOVER DAN SALES GROWTH TERHADAP NET PROFIT MARGIN - Elsa Pitriani; Kokom Komariah; Dicky Jhoansyah (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2024)
The objectives of this study are 1) To find out Working Capital Turnover, Inventory Turnover, Sales Growth and Net Profit Margin in manufacturing companies in the consumer goods industry sector for the period 2019 - 2021 2) To determine Working Capital Turnover has an effect on Net Profit Margin in manufacturing companies in the consumer goods industry sector for the period 2019 - 2021 3) To find out Inventory Turnover affects Net Profit Margin in manufacturing companies in the consumer goods industry sector for the period 2019 - 2021 4) To find out Sales Growth affects Net Profit Margin in manufacturing companies in the consumer goods industry sector for the period 2019 - 2021. The research method used by this researcher is Quantitative research with Descriptive and Associative approaches because the data is in the form of numbers and is explained in the form of graphs, charts, and diagrams. The results of this study are Working capital turnover on net profit margin has a significant effect. Inventory turnover on net profit margin does not have a significant effect. Sales growth on net profit margin has no significant effect.